Speed, change of direction speed and reactive agility in adolescent soccer players: a comparative study - Gucic, M.; Andracic, S.; Molnar, S.; Cvetkovic, M. (XX Scientific Conference in physical education, sport and recreation - (Nis, Serbia, october 19-21st, 2017) - Book of Proceedings, 2017)
We investigated age-related differences in speed, change of direction speed and reactive agility in a group of highly trained adolescent soccer players. A total of 75 adolescent male soccer players (aged 14. 19 years) were recruited. The players were grouped on the basis of chronological age into 2-year age categories: under 15 (U15: 12.0.13.9 years), under 17 (U17: 14.0.15.9 years), and under 19 (U19: 16.0.17.9 years). Players were tested for 5, 10-m sprint, and 20-m sprint, and agility performance (COD, Illinois test and reactive agility test). Under 19 players had faster (p .0.01) 20-]m and illinois (p .0.01) times than U15 players, while U17 players were faster (P .0.05) than U15 players in 20 sprint, COD right and illinois test performances. The main finding of this study was that no significant differences were found among the players in different age categories for most of the variables.